Building Organizational Resilience: Four Configurations - Burnard, Kevin; Bhamra, Ran; Tsinopoulos, Christos (IEEE transactions on engineering management, 2018)
This paper empirically explores the organizational processes at the onset of disruptions and the factors that determine different configurations of responses. It examines how processes of response, both before and in the aftermath of a disruption, support the building and development of organizational resilience. Using case study data from three U.K. based organizations, this paper makes the following three contributions. First, it identifies the common elements involved in decision making at the onset of a disruption, and explains the iterative stages and processes that led to the development of resilience. It explains the criticality and relationships between the elements of detection, activation, and response. Second, this paper explains why responses vary from one situation to another, by identifying two dimensions that determine the configurations of organizational resilience, namely Preparedness and Adaption. Third, this paper presents the resilience configurations matrix that gives rise to and establishes four distinct types of organizational configurations, which are Process Based, Resourceful, At High Risk, and Resilience Focused. This paper concludes by discussing the implications for theory and practice of resilience.